PENGARUH KUALITAS PRODUK, INOVASI PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK HI JACK SANDALS BANDUNG - admin admin; Diah Ernawati (JWM (JURNAL WAWASAN MANAJEMEN), 2019)
This study aims to determine and analyze the influence of product quality, product innovation and promotion to product purchase decision of "Hi Jack Sandals Bandung". Data were collected by questionnaire distribution technique using Likert scale. The population in this study was obtained from the transaction data "Hi Jack Sandals Bandung" in January-July 2017 amounted to 3,033 transactions.The sample wasselected using purposive sampling obtained100 respondents. Hypothesis testing in this study usingclassical assumption test, multiple linear regression with α 0,05, whichdetermine, fit test model (F test), and t test with SPSS Program version 24. The results of this study indicate that variables of product qualityand promotion have significant positive effectson purchase decision,while variable of product innovation has no significant effect on purchase decision.